12-lead post-ROSC electrocardiogram discriminates survival to hospital discharge. A sub-analysis of the PEACE study. (2nd May 2022) - Gentile, FR; Baldi, E; Schnaubelt, S; Caputo, ML; Clodi, C; Bruno, J; Compagnoni, S; Benvenuti, C; Domanovits, H; Burkart, R; Primi, R; Ruzicka, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Once the return of spontaneous circulation (ROSC) after an out-of-hospital cardiac arrest (OHCA) is achieved the acquisition of a 12-lead electrocardiogram (ECG) is strongly recommended in order to determine candidates for urgent coronary angiography. However, little is known so far about the association of ECG features and survival to hospital discharge in OHCA patients. Purpose: The aim of the present study is to assess whether ECG features could be associated with survival to hospital discharge. Methods: We analysed all the post-ROSC ECGs collected from January 2015 to December 2018 in three European centres. For every ECG, the main features were analysed and filed in the database together with the pre-hospital data collected for every patient according to the Utstein style. Every ECG was evaluated by two independent cardiologists and in case of doubt a third one was asked to solve the dispute. Results: We collected 370 ECGs: 287 males (77.6%); median age 62 years old (IQR 53-70 years); 121 from center 1 (32.7%), 38 from center 2 (10.3%) and 211 from center 3 (57.0%). In Cox univariable regression, age older than 62 years [HR 1.7 (95%CI 1.1-2.4), p=0.007], QRS wider than 120 msec [HR 1.87 (95%CI 1.3-2.7), p<0.001], the presence of ST elevation in more than one segment [HR 1.7 (95%IC 1.2-2.5), p=0.003], the presence of left bundle branch block (LBBB) [HR 1.7 (95%CI 1.1-2.9), p=0.03] and the presence of a right bundle branch block [HR 1.8 (95%CI 1.1-2.8), p=0.01] were associated with death before hospital discharge. In multivariable Cox regression, after correction for the ROSC-to-ECG time, age older than 62 years [HR 1.6 (95%CI 1.1-2.3), p=0.01], QRS wider than 120 msec [HR 1.7 (95%CI 1.2-2.5), p=0.004] and the presence of ST elevation in more than one segment [HR 1.7 (95%CI 1.2-2.5), p=0.004] were confirmed to be independently associated with death before hospital discharge. By assigning one point to each one of these three variables, we have created a score ranging from 0 to 3. The rate of survival to hospital discharge was found to be significantly different in the four categories [score=0: 80.8%; score=1: 71.2%; score=2: 61.9%; score=3: 34.4%; p<0.001, p for trend <0.001]. Lastly, with a Cox regression model, assuming score 0 as a reference, we confirmed how scores 2 or 3 were significantly associated with death before hospital discharge [HR 1.9 (95%CI 1-3.5), p=0.037 e HR 5.1 (95%CI 2.6-10.1), p<0.001 respectively]. Conclusions: Our study proves that after an out-of-hospital cardiac arrest, post-ROSC ECG features can be used for prognostic stratification in addition to the selection of patients who may benefit from urgent coronary angiography.